PENGARUH WORK DEMANDS TERHADAP TECHNOSTRESS MELALUI EMPLOYEE WELL - BEING KARYAWAN - Icho , Icho Alfiando; Fachrudy Asj'ari (Majalah Ekonomi, 2025)
This study analyzes the motivations behind fraudulent activities in Small and Medium Enterprises (SMEs) in Surabaya, focusing on those with an annual turnover ranging from IDR 300 million to IDR 50 billion. The research adopts the Fraud Triangle theory to examine the factors contributing to fraudulent behavior within organizations. A quantitative approach with Partial Least Squares (PLS) analysis is used to test three primary factors: pressure, opportunity, and rationalization, which influence fraudulent actions. The findings suggest that weak internal control systems, financial pressures, and the absence of ethical guidelines are significant contributors to fraud in SMEs. Data was collected through surveys from 100 SMEs in Surabaya, and the analysis shows that the relationship between these factors and fraudulent behavior is statistically significant. The study concludes that strengthening internal control systems and fostering a culture of transparency within organizations are essential steps to reduce the risk of fraud in SMEs. These insights can provide valuable guidance to policymakers and business owners in Surabaya in developing more effective strategies to prevent fraud and enhance the overall integrity of the business environment..   Keywords                    : Fraud Triangle; Internal Control; Opportunity; Pressure; Rationalization